2007
DOI: 10.1007/bf02877708
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival flora in patients with type 1 or type 2 diabetes mellitus

Abstract: Patients with diabetes mellitus (DM) are prone to infection because glucose in the skin, urine, mucous membranes, and tears promotes growth of microorganisms. Conjunctival flora develops soon after birth, and some saprophytic conjunctival flora play a pathogenic role when immune function is compromised, which can lead to serious infection. DM is one condition that may compromise immune status. In lacrimal function tests of DM patients, a decrease in breakup time (BUT) of lacrimal film and a decrease in Schirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 20 publications
1
36
2
2
Order By: Relevance
“…In one of the two small-sized studies published on the diabetics conjunctival bacteria, 28,29 an increased prevalence of S. aureus was only found in diabetics type II, although the number of patients studied by Bilen et al 28 was small (17 diabetics type I, 66 diabetics type II, and 50 control subjects). But only an increased prevalence of SCN was found in the other one, 29 which only studies the flora of diabetics with retinopathy.…”
Section: Discussionmentioning
confidence: 95%
“…In one of the two small-sized studies published on the diabetics conjunctival bacteria, 28,29 an increased prevalence of S. aureus was only found in diabetics type II, although the number of patients studied by Bilen et al 28 was small (17 diabetics type I, 66 diabetics type II, and 50 control subjects). But only an increased prevalence of SCN was found in the other one, 29 which only studies the flora of diabetics with retinopathy.…”
Section: Discussionmentioning
confidence: 95%
“…42 To our knowledge, the present study contains the biggest cohort of consecutive patients undergoing their first cataract surgery in which a wide range of individual co-morbidities were associated with the prevalence of their conjunctival bacteria. Previously, Fahmi et al 27 found a correlation between male sex and the prevalence of Corynebacteria and Gram-negative rods; other small studies associated the conjunctival bacteria with a particular co-morbidity such as patients taking immunosuppressive drugs 31 or those having diabetes; 32,33 Miñ o de Kaspar et al 29 found that advanced age and patients grouped for having diabetes, immunosuppression, autoimmune conditions, and asthma had a higher rate of positive conjunctival cultures than the control group, but they did not find any gender association. Recently, 30 with fewer patients, no association was found between conjunctival bacterial prevalence and diabetes, steroid therapy, dialysis and allergic conjunctivitis, but an association was found with age above 60.…”
Section: Discussionmentioning
confidence: 98%
“…[27][28][29][30] However, very little is known about whether the clinical characteristics of this small number of patients with pathogenic bacteria colonising their conjunctivas are different. 16,[31][32][33] Today, the available data of the Human Microbiome Project reveals the possibility of determining differences between the microbiomes of healthy and unhealthy people. 34 This fact opens a new horizon in the management of infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…S. epidermidis, S. aureus, and Corynebacterium sp have also been found in diabetic patients (4) . Variations in conjunctival microbiota may occur due to both intrinsic and extrinsic changes in the body, such as geographical diversity and different socioeconomic characteristics (4,10,(12)(13)(14) . Therefore, the conjunctival aerobic microbiota of diabetic patients was studied in two different Brazilian cities: Rio Branco, in the state of Acre, in north Brazil; and Sorocaba, in the state of São Paulo, in southeastern Brazil.…”
Section: Introductionmentioning
confidence: 99%